Design and Optimization of Modular Fixture Using Finite Element Method for Cylindrical Parts - Khan, Awais Ahmad; Ahmad, Naseer; Saleem, Kamran; Mughal, Khurram Hameed; Bubvi, Salman Abubakar; Ahmad, Shaiq (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
To ensure the production of high-quality parts, a precise fixture is essential in minimizing the workpiece displacement while maintaining positional accuracy, stability, and avoiding interference with the cutting tool. Workpiece deformation during machining operations can be curtailed by adequate selection, number, and position of locators/clamps. This work integrates advanced finite element method (FEM) simulations to accurately predict and optimize the performance of modular fixtures, improving precision, flexibility, and efficiency of the manufacturing process. An optimized fixture layout design methodology is proposed, enabling attainment of these machining objectives for quality work on solid and thin-walled cylindrical parts. In addition to geometric optimization, clamping forces are refined using the force-moment method, minimizing workpiece deformation and improving hold accuracy. The optimal layout is determined with minimal sample runs and implemented for drilling 14.5 mm diameter holes in Al-T3 pipes used in the HVAC systems of SANPAK Pvt. Ltd. The experimental results obtained after the modular fixture optimization through FEM were found to increase the accuracy of hole (rejection rate drop from 5% to 2%) and reduction in setup time and efficiency of process. A chi-square test confirmed the significance of this improvement (χ² = 20.05, p < 0.00001). The unique study integrates multiple parameters, such as clamping force, deformation, and stability, in a single framework, for a comprehensive and improved solution to the challenges of fixture design for cylindrical parts. This approach enhances the overall effectiveness, adaptability, and cost of modular fixture design and provides manufacturing solutions applicable to diverse industrial components.